2011
DOI: 10.1002/mrd.21304
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hsf1, Hsf2, and Phlda1 in cells undergoing cryptorchid‐induced apoptosis in rat testes

Abstract: Surgery-induced cryptorchidism, in which the testes are prevented from descending into the scrotal sac, results in testicular germ cell death, and it is commonly used as an experimental tool in the study of spermatogenesis. However, the molecular events underlying the activation of germ cell death remain poorly understood. In the present study, we investigate selective cell loss from cryptorchid rat testis by using DNA flow cytometry and by determining protein and mRNA expression of Hsf1, Hsf2, and Phlda1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 41 publications
(44 reference statements)
1
7
0
2
Order By: Relevance
“…Moreover, PHLDA1 did not accumulate after heat shock in any type of spermatogenic cells through the apoptosis was induced and DNA breaks were detected 4-6 h after the treatment, especially in spermatocytes (Figure 2b). On the other hand, in agreement with a previously published report [10], PHLDA1 accumulated in cryptorchid testes 14 days after surgery, also in spermatogenic cells. However, the accumulation of apoptotic cells in cryptorchid testes could be detected earlier than PHLDA1 up-regulation (7 days, but not 14 days after surgery; Figure 2c; see also [7]).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, PHLDA1 did not accumulate after heat shock in any type of spermatogenic cells through the apoptosis was induced and DNA breaks were detected 4-6 h after the treatment, especially in spermatocytes (Figure 2b). On the other hand, in agreement with a previously published report [10], PHLDA1 accumulated in cryptorchid testes 14 days after surgery, also in spermatogenic cells. However, the accumulation of apoptotic cells in cryptorchid testes could be detected earlier than PHLDA1 up-regulation (7 days, but not 14 days after surgery; Figure 2c; see also [7]).…”
Section: Resultssupporting
confidence: 93%
“…However, analysis of PHLDA1-induced cell death was not apoptosis-specific in the above study because cells adhering and detaching from dishes were simply counted leaving room for other types of cell death (e.g., anoikis). HSF1/PHLDA1 pathway was also suggested to have a role in cell death of primary spermatocytes in cryptorchid rat testes [10]. However, in this model, the highest level of apoptosis was observed before the accumulation of the PHLDA1 protein.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Yin et al revealed that cryptorchidism induced germ cell apoptosis in an experimental mouse model via p53-dependent and p53-independent pathways [ 23 ]. Liu et al also found that the Hsf1/Phlda1 pathway participated in primary spermatocyte apoptosis in surgery-induced cryptorchid testes of rats [ 27 ]. The expression of many apoptosis-related miRNAs was also shown to be altered in post-cryptorchidopexy testicular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSF1 is able to directly bind to and activate PHLDA1 in response to heat shock in male germ cells (27). Furthermore, during a time-course induction of cryptorchidism in rat testes, HSF1 and PHLDA1 were strongly expressed, suggesting that the HSF1/PHLDA1 pathways have an important role in the apoptosis of primary spermatocytes in cryptorchid testes (28).…”
Section: Phlda1 Expression and Cell Deathmentioning
confidence: 99%